Implementasi Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Kurikulum Merdeka di Pondok Pesantren Daarussunnah Wangon - Aji Nurantono; Syamsul Hidayat; Muthoharun Jinan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by implementing the independent curriculum in all educational institutions under the Ministry of Education and the Ministry of Religion, where this regulation requires formal educational institutions, both those with full-day and boarding status, to implement the independent curriculum. The Daarussunnah Wangon Islamic Boarding School is one of the institutions with an Islamic boarding school background that implements this curriculum. This is because the Daarussunnah Wangon Islamic boarding school carries out formal education under the auspices of the Ministry of Religion at the MTs and MA levels. As one of the formal Islamic boarding schools that implements an independent curriculum, it cannot be separated from various problems in its implementation. Among them; are delays in the socialization of the independent curriculum, adjustments to the curriculum by combining the independent curriculum and Islamic boarding schools, and limited movement of Islamic boarding schools in the Pancasila student project scheme. The aims of this research are (1) to find out the implementation of the independent curriculum at the Daarussunnah Wangon Islamic Boarding School, (2) to find out the implementation of the project to strengthen the profile of Pancasila students at the Daarussunnah Wangon Islamic Boarding School.